Otolith-based age and growth of the spotted moray eel (Gymnothorax moringa) and squirrelfish (Holocentrus adscensionis) from Ascension Island and St Helena - Valerio Visconti; Elizabeth D. L. Trip; Ian Woodgate; Tiffany Simpson; James B. Bell; Paul Whomersley; Leeann Henry; Kirsty Jones; Kyne Krusic-Golub; Simon Robertson; Serena Wright (Frontiers in Marine Science, 2025)
This study investigates the age-based life-history traits of two groundfish species, the spotted moray eel ( Gymnothorax moringa ) and squirrelfish ( Holocentrus adscensionis ), found in Ascension Island and St Helena. Both islands are part of the UK Overseas Territories (UKOTs) and are known for their fish biodiversity. The research aims to provide essential life-history information to support sustainable management of these species within the Marine Protected Areas (MPAs) of Ascension Island and St Helena. A total of 556 fish samples were collected between 2014 and 2021, with 279 individuals of G. moringa and 277 individuals of H. adscensionis . We found significant differences in life span, adult body size, and growth rates between the two islands for both species. G. moringa exhibited longer life spans (32 vs 29 years) and faster growth rates at Ascension Island compared to St Helena, while H. adscensionis showed larger adult sizes at Ascension Island but shorter life spans (21 vs 27 years) compared to St Helena. The study highlights the importance of developing locality-specific species life history data collections to monitor population dynamics in MPA areas. This biological information is essential to allow future assessment programs on the potential impacts of climate change and inshore human activities, including the impacts of inshore fisheries. Future research should focus on reproductive biology, size and age at maturity, and migration patterns to enhance the accuracy of sustainability assessments for these fisheries.